Influence of structural nonlinearities in stall-induced aeroelastic response of pitching airfoils - Pereira, Daniel A. (2014)
Stall-induced vibrations are a relevant aeroelastic problem for very flexible aero-structures. Helicopter blades, wind turbines, or other rotating components are severely inflicted to vibrate in stall condition during each revolution of its rotor. Despite a significant effort to model the aerodynamics associated to the stall phenomena, non-linear aeroelastic behavior prediction and analysis in such flow regime remain formidable challenges. Another source of nonlinearity with influence to aeroelastic response may be associated to structural dynamics. The combination of both separated flow aerodynamic and structural nonlinearities lead to complex dynamics, for instance, bifurcations and chaos. The purpose of this work is to present the analysis of stall-induced vibrations of an airfoil in pitching when concentrated nonlinearities are associated to its structural dynamics. Limit cycles oscillations at higher angles of attach and complex non-linear features are analyzed for different nonlinear models for concentrated restoring pitching moment. The pitching-only typical section dynamics is coupled with an unsteady aerodynamic model based on Beddoes-Leishmann semi-empirical approach to produce the proper framework for gathering time series of aeroelastic responses. The analyses are performed by checking the content of the aeroelastic responses prior and after limit cycle oscillations occur. Evolutions on limit cycles amplitudes are used to reveal bifurcation points, thereby providing important information to assess, characterize, and qualify the nonlinear behavior associated with combinations of different forms to represent concentrated pitching spring of the typical section.